Olympic coaching excellence: A quantitative study of Olympic swimmers` perceptions of their coaches - Cook, G. M.; Fletcher, D.; Peyrebrun, M. (Journal of Sports Sciences, 2022)
Although coaching is a co-created process, researchers investigating the psychological aspects of Olympic coaching have tended to overlook the perceptions of athletes and whether these distinguish between performance-related outcomes. The objective of this research was to examine whether athletes` perceptions of their coaches discriminate between world-leading (i.e., Olympic gold medal winning) and world-class (i.e., Olympic non-gold medal winning) coaches. Observer-reported psychometric questionnaires were completed by 38 Olympic swimmers who had collectively won 59 Olympic medals, of which 31 were gold. The questionnaires assessed perceptions of 12 variables within the Big Five personality traits, the dark triad, and emotional intelligence, and the data was analyzed using three one-way multivariate analysis of variance and follow-up univariate F-tests. The results showed that world-leading coaches were perceived to be significantly higher on conscientiousness, openness to experience, perception of emotion, and management of others emotion, and lower on narcissism, than world-class coaches. This suggests that athletes` perceptions of their coaches may discriminate between world-leading and world-class coaches. The implications for coaches` psychological development are discussed and compared with previously reported Olympic coaches` perceptions of themselves.